Racial/Ethnic Differences in Health-Related Quality of Life Among Gay and Bisexual Prostate Cancer Survivors - Bates, Alex J.; Rosser, B. R. Simon; Polter, Elizabeth J.; Wheldon, Christopher W.; Talley, Kristine M. C.; Haggart, Ryan; Wright, Morgan; Mitteldorf, Darryl; West, William; Ross, Michael W.; Konety, Badrinath R.; Kohli, Nidhi (Frontiers in Oncology, 2022)
Abstract Introduction: Prostate cancer treatment has established effects on the health-related quality of life (HRQOL) of patients. While racial/ethnic differences in HRQOL have been explored in heterosexual patients, this is the first study to examine racial/ethnic differences in a cohort of sexual minority prostate cancer survivors. Methods: We used data from the Restore-1 study, an online cross-sectional survey of SGM prostate cancer survivors in North America, to explore the association between race/ethnicity and HRQOL. General mental and physical HRQOL was assessed using the Short-Form Health Survey (SF-12). The frequency and distress of prostate cancer specific symptoms was assessed using the Expanded Prostate Cancer Composite (EPIC) scale. Multivariable linear regression was used to estimate mean differences in HRQOL between sexual minority men of color and their white, non-Hispanic counterparts after adjustment for pertinent demographic and medical characteristics. Results: Among 191 participants, 23 (12%) self-identified as non-white and/or Hispanic. In unadjusted analysis, sexual minority men of color compared to their white counterparts reported worse HRQOL scores in the EPIC hormonal summary (73.8 vs. 81.8) and hormonal function (70.9 vs 80.4) domains. Clinically important differences between men of color and their white counterparts were seen in the EPIC bowel function (mean difference (MD): -4.5, 95% CI: -9.8, 0.8), hormonal summary (MD: -8.0, 95% CI: -15.5, -0.4), hormonal function (MD: -9.5, 95% CI: -17.5, -1.6), and hormonal bother (MD: -6.6, 95% CI: -14.3, 1.1) domains. After adjustment for covariates, there were no statistically-or-clinically significant differences in HRQOL scores between sexual minority men of color and white, non-Hispanic participants. Conclusions: This study provides the first evidence that sexual minority men of color may have similar HRQOL outcomes compared to white, non-Hispanic sexual minority men following prostate cancer treatment.